Angiosome-directed endovascular intervention and infrapopliteal disease: Intraoperative evaluation of distal hemodynamic changes and foot blood volume of lower extremity - Wang, Chaonan; Chen, Junye; Lei, Jinsong; Shao, Jiang; Lai, Zhichao; Li, Kang; Cao, Wenteng; Liu, Xiaolong; Yuan, Jinghui; Liu, Bao (Frontiers in Surgery, 2022)
Objectives: To evaluate foot blood volume and hemodynamics and explore whether quantitative techniques can guide revascularization. Materials and methods: A prospective single-center cohort study included thirty-three patients with infrapopliteal artery occlusion who underwent percutaneous transluminal angioplasty (PTA) between November 2016 and May 2020. The time-to-peak (TTP) from color-coded quantitative digital subtraction angiography (CCQ-DSA) and parenchymal blood volume (PBV) were used to evaluate the blood volume and hemodynamic changes in different regions of the foot before and after the operation. Results: After the intervention procedure, the overall blood volume significantly increased from 25.15±21.1 ml/1000 ml to 72.33±29.3 ml/1000 ml (p<0.001, with an average increase of 47.18 ml/1000 ml. The overall TTP decrease rate, postoperative blood flow time significantly faster than those preoperatively, from 22.93±7.83 to 14.85±5.9 s (p<0.001, with an average decrease of 8.08 s). Direct revascularization (DR) resulted in significant blood volume improvement than compared with indirect revascularization (IR) [188% (28, 320) vs.51% (10, 110), p=0.029]. Patients with DR had a significantly faster blood flow time than those with IR [80% (12, 180) vs. 26% (5, 80), p=0.032]. The ankle-brachial index (ABI) of the affected extremity also showed an significant change from 0.49±0.3 to 0.63±0.24 (p<0.001) after the intervention. The relative values of ΔTTP and ΔABI showed a weak correlation (r= -0.330). Conclusions: The quantitative measurement results based on PBV and CCQ-DSA techniques showed that the overall blood volume increased significantly and that the foot distal hemodynamics were significantly improved after endovascular treatment. DR in the ischemic area could r improve foot perfusion.